2021
DOI: 10.4102/jef.v14i1.617
|View full text |Cite|
|
Sign up to set email alerts
|

Corporate life cycle and dividend payout: A panel data analysis of companies in an emerging market

Abstract: Background: The dividend payout policy remains one of the key functional areas of corporate finance because it is through receipt of dividends that shareholders can share in the profits of their investments. Amongst the dividend payout theories that have been developed over the decades, the life-cycle hypothesis has received little attention in research.Aim: The aim of this study was to test the dividend life-cycle hypothesis in the South African contex.Motivation for the study: Justification for this study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…𝑉 𝑖 : Represent unobservable factors that are unchanged following the time ɛ 𝑖𝑡 : Represent unobservable factors that are fluctuated following the time In addition, in order to remedy the common errors, such as multicollinearity, autocorrelation, and heteroskedasticity in panel data. The advanced estimator is a generalized method of moments (GMM) that will be employed following Munzhelele et al (2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…𝑉 𝑖 : Represent unobservable factors that are unchanged following the time ɛ 𝑖𝑡 : Represent unobservable factors that are fluctuated following the time In addition, in order to remedy the common errors, such as multicollinearity, autocorrelation, and heteroskedasticity in panel data. The advanced estimator is a generalized method of moments (GMM) that will be employed following Munzhelele et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…According to the above test, the author concludes that the model faces some statistical errors such as heteroskedasticity and autocorrelation phenomenon. Therefore, the author uses the model GMM to remedy these phenomenon as Munzhelele et al (2021) and the result is shown in Table 8. The discussion of this study will rely on the regression results with the GMM model.…”
Section: Remedy the Statistical Errorsmentioning
confidence: 99%
“…According to Francis and Osborne (2012) and Lee and Hsieh (2013), several estimators can be adopted in the dynamic panel data model, which include the ordinary least squares (OLS), the differenced generalised methods of the moment (Diff GMM) of Arellano and Bond (1991), the system generalised methods of the moment (Sys GMM) of Blundell and Bond (1998), and the least-squares dummy variable correction (LSDVC) proposed by Bruno (2005). Numerous studies such as Andres et al (2009), Munzhelele et al (2021Munzhelele et al ( , 2022, and Obadire et al (2022a) successfully adopted this combination of dynamic panel estimators. The Diff-GMM is essential for estimating dynamic panel data models, particularly when endogeneity is a concern, as it transforms the data to eliminate fixed effects and offer robust parameter estimation using moment conditions.…”
Section: Choice Of Model Estimation Proceduresmentioning
confidence: 99%